Tailoring of tensile and dynamic thermomechanical properties of interleaved chemical-treated fine almond shell particulate flax fiber stacked vinyl ester polymeric composites. (November 2019) - Ramraji, K; Rajkumar, K; Sabarinathan, P
Natural fiber and particulates are being exploited to attain eco-friendly products for construction and automotive sectors. These sectors are moving towards the use of high damping characteristic natural biofibers and particulate-reinforced polymer composite as part of the structural components. In this work, woven flax fiber (0° and 90°) and almond shell particulates were used. They were subsequently treated with alkaline and acetylene chemical solution separately. Polymer composite laminates were prepared using a vinyl ester resin as matrix and by stacking flax fibers and almond particulates interleaved in an alternative sequence using the hand layup technique. This was followed by hydraulic pressing. Composite laminates were fabricated by varying the almond shell particulate weight fraction of 0%, 5%, 10%, and 15%. Mechanical properties such as tensile and flexural strength were experimentally measured. Dynamic thermomechanical analysis was conducted on the alkaline-treated and untreated composites with different frequencies for the assessment of the damping characteristics. The alkaline-treated interleaved almond shell and flax fiber composite showed considerably higher damping characteristics. This could be due to the improved adhesion between the matrix and reinforcements. An addition of almond shell particulate positively increased the strength and stiffness of composites.